Components and Pharmacodynamical Mechanism of Yinfupian Based on Liquid Chromatography-Mass Spectrometry and Proteomics Analyses - Tong, Heng-li; Chen, Hao; Gong, Fei-peng; Zhong, Ling-yun; Zhu, Jing; Yang, Song-hong (Frontiers in Pharmacology, 2021)
Objective: According to the treatment records of Yang deficiency syndrome (YDS) with characteristic decoction pieces of lateral root of Aconitum carmichaelii —Yinfupian (YF) in traditional Chinese medicine prepare school, known as “Jianchangbang”. The aim of this study was to investigate differences in the composition and therapeutic mechanism of the unprocessed lateral root of Aconitum carmichaelii (ULRA) and its processed product (YF). Methods: Ultra-performance liquid chromatography-quadrupole time-of-flight mass spectrometry and orthogonal partial least squares discriminant analysis method were used to determine and screen the main components of ULRA and YF. Changes in the histological structure and morphology of gonads in rats were observed using hematoxylin-eosin. Enzyme-linked immunosorbent assay was used to determine the contents of serum cyclic adenosine monophosphate and cyclic guanosine monophosphate in YDS rats treated with ULRA and YF. Tandem mass tag proteomics analysis was used to identify the differentially expressed proteins in YDS rats treated with ULRA and YF. Results: Both ULRA and YF exerted certain therapeutic effects on rats with YDS. They improved the gonadal morphology and increased the contents of serum cyclic adenosine monophosphate and cyclic guanosine monophosphate. After processing of ULRA into YF, the content of C19-diester-diterpenoid alkaloids decreased (converted into C19-monoester-diterpenoid alkaloids and C19-alkylol amine-diterpenoid alkaloids), whereas that of C20-diterpene alkaloids increased. Proteomics analysis showed that cytochrome P450 and aldehyde oxidase 3 (AOX3) were downregulated, whereas cathepsin G (CTSG) was upregulated in rats with YDS. Treatment with ULRA mainly downregulated the expression of α-actinin, fast skeletal troponin, creatine kinase, and myosin. Treatment with YF mainly upregulated the expression of mitochondrial ribosomal protein and mitochondrial inner membrane protein. Conclusion: ULRA and YF exerted good therapeutic effects on YDS; the main difference in components between these preparations was in C19-diterpenoid alkaloids. ULRA mainly acts on the muscle contraction-related proteins and is closely related to inflammation and myocardial injury. YF mainly acts on the mitochondrial proteins and is closely related to adenosine triphosphate energy metabolism.